Vila Cristiana: The landscape as an emancipatory agenda - Magalhães, Kelly Cristina (Latin American Journal of the Built Environment & Sustainability, 2025)
Objective – This article presents the concept of landscape from an emancipatory perspective, drawing on a laboratory practice in which research and outreach merge to elucidate public policies at the municipal level. Methodology – The research method used is the recognition and mapping of landscape attributes with the aim of valuing these elements and consulting with populations, who for centuries have remained without access to inclusive public policies, highlighting their potential to foster a more harmonious coexistence between humanity and nature. Originality/Relevance – Environmental racism, a term coined by Franklin Chavis, a Black activist in North America, in 1982, is the most concrete form of racism that emerges from social inequalities and drives socio-spatial exclusion, resulting in the constant and complex invisibility of the Black population in sub-standard housing and precarious settlements in large and small cities. Analyzing the landscape from this perspective invites us to reflect on the role of environmental activism and the need for an intersectional approach that considers the multiple dimensions of social struggles. Results – The result is the construction of an understanding of the connection between city and forest, aiming to understand the relationship between the populations living amidst remnants of the Cerrado and the fragments of vegetation predominant in the site where the city of Bauru developed. We highlight aspects of the problems arising from the difficulty of establishing a fair land policy, such as access to land as a dimension of the notion of territory. This premise enabled an investigation into the conditions of access to housing based on an approach to social movement settlements in the city under study. Finally, we present the city as a laboratory based on a Landscape Analysis Roadmap with the purpose of outlining a landscape project. Theoretical/Methodological Contributions – The interaction between technicians and the community, based on knowledge of the landscape, enabled the identification of needs and aspirations, revealing an essential participatory principle for advancing a spatial justice agenda in practice. Likewise, popular participation, based on in-depth historical and environmental knowledge, enabled the community to identify and acknowledge the different features of the landscape. Social and Environmental Contributions – Finally, we must consider that analyzing the landscape from the perspective of consulting a less-assisted landscape invites us to reflect on the need for an approach that considers the agenda of social struggles as a basis for building a more just and socially balanced city. Revolutionary practice, by integrating issues of race, class, and gender into discussions about landscape, contributes to building a more just and sustainable future, where everyone has a voice and a say in shaping the environment they inhabit.